Cellular Dissociation Grading Based on the Parameters Tumor Budding and Cell Nest Size in Pretherapeutic Biopsy Specimens Allows for Prognostic Patient Stratification in Esophageal Squamous Cell Carcinoma Independent From Clinical Staging. (May 2019) - Jesinghaus, Moritz; Brühl, Frido; Steiger, Katja; Klare, Peter; Reiser, Marianne; Scheiter, Alexander; Konukiewitz, Björn; Kuhn, Peer; Münch, Stefan; Quante, Michael; Schmid, Roland M.; Wilhelm, Dirk; et al.
Abstract : Initial treatment planning in esophageal squamous cell carcinoma mainly relies on clinical staging. Recently, a highly prognostic grading system based on the cellular dissociation parameters Tumor Budding and Cell Nest Size has been proposed for resected esophageal squamous cell carcinoma. To probe for the transferability and relevance of this established novel grading system in the pretreatment setting, we evaluated Tumor Budding/Cell Nest Size in pretherapeutic biopsies of either primarily resected (cohort 1, n=80) or neoadjuvantly treated (cohort 2, n=75) esophageal squamous cell carcinoma. Grading data were correlated with clinicopathologic and survival parameters. High Tumor Budding Activity and small Cell Nest Size in pretherapeutic biopsies were strongly associated with shortened overall survival, disease-free survival, and disease-specific survival in both cohorts. A modified histopathologic grading system incorporating both factors termed "Cellular Dissociation Grade" showed excellent prognostic demarcation between well (G1), moderately (G2), and poorly differentiated (G3) carcinomas in both scenarios (overall survival: cohort 1: P <0.001; cohort 2: P =0.009) and was predictive for a high pathologic tumor stage and the presence of nodal metastases in primarily resected patients. Multivariate analyses revealed the Cellular Dissociation Grade to be a predictor of poor outcome in the pretherapeutic setting independent of clinical stage (overall survival, disease-free survival, and disease-specific survival: P <0.001). Hazard ratio for disease-free survival was 3.19 for G2 and 5.66 for G3 carcinomas compared with G1 neoplasms. Our data not only prove the transferability of histopathologic grading based on Tumor Budding/Cell Nest Size to biopsy specimens in esophageal squamous cell carcinoma, but also demonstrate that the Cellular Dissociation Grade is a strong outcome predictor in this entity even in the pretreatment scenario. Therefore, we believe that this novel type of grading has the ability to serve as a powerful histology-based pretherapeutic biomarker, that might supplement clinical staging for choosing the most suitable therapy decision. Abstract : Supplemental Digital Content is available in the text.